Lincoln's Forgotten Ally : Judge Advocate General Joseph Holt of Kentucky - Leonard, Elizabeth D. (Book collections on Project MUSE., 2011)
Joseph Holt, the stern, brilliant, and deeply committed Unionist from Kentucky, spent the first several months of the American Civil War successfully laboring to maintain Kentucky's loyalty to the Union, then went on to serve as President Lincoln's judge advocate general. This book offers a full-scale biography of Holt, who has long been overlooked and misunderstood by historians and students of the war.